1. Nyay-vartika-tatparyaparisuddhi of Udayanacharya Vol. IV 2. Nyaya-vartika-tatparya-tika of Vachaspati Misra Vol. III - Krishna, B V Venkata (Journal of Dharma, 1999)
1. Nyay-vartika-tatparyaparisuddhi of Udayanacharya, Vol. IV, Nyayachatur-granthika Series, pp.709. ISBN 81-85636-28-1. 2. Nyaya-vartika-tatparya-tika of Vachaspati Misra, Vol. III, pp.604. ISBN 81-85536-26-5 ed. Ananthalal Thakur, New Delhi: Indian Council of Philosophical Research, 1996.